Efficiency of a music-based intervention as an adjunct to the first noninvasive ventilation session in acute exacerbation of COPD: A randomized single-blind controlled trial protocol - Imen Ben Saida; Dhekra Chebil; Wassim Jomaa; Marwa Zghidi; Khalil Attia; Mohamed Boussarsar (PLoS ONE, 2025)
Introduction Noninvasive ventilation (NIV) is a cornerstone in the management of Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD). The aim of this study is to assess the impact of music-based intervention on the efficiency of NIV in patients with AECOPD. Methods It’s a prospective, randomized, single-blinded, parallel-group trial. Critically ill COPD patients admitted for acute exacerbation and eligible for NIV will be included. Patients in the control group will receive only NIV. In the intervention group, patients will receive NIV with music-based intervention. The music will be delivered through headphones. Both groups will receive standard care in accordance with current clinical guidelines. The primary endpoint is the change in arterial Pressure of Carbon dioxide PaCO2, defined as the difference between baseline PaCO₂ (prior to NIV initiation) and PaCO₂ measured after 4 hours. Secondary endpoints will be recorded at different time points: change of PaCO2 over time (h0, h2, h4), unplanned interventions, changes in respiratory and cardiovascular parameters (h0, h2, h4), changes in Respiratory comfort (h0, h2, h4), Borg Dyspnea Scale (h0, h2, h4), Verbal Numeric Rating Scale for pain assessment (h0, h2, h4), Encephalopathy score (h0, h2, h4), Richmond Agitation-Sedation Scale (h0, h2, h4), and psychological assessment (Rapid Clinical Test For delirium, State Trait Anxiety Inventory, perceived stress scale) (h0, h4). Discussion This study is expected to contribute reliable scientific evidence for the optimal management of AECOPD, potentially reducing the need for intubation and mechanical ventilation and their associated complications. Trial registration The study was prospectively registered on the Pan African Clinical Trial Registry within the number PACTR202501862862010.